Structural Design of City Railway Underground Depot with Reserved Conditions for Overlying Property Development - TAN Qifeng (Chengshi guidao jiaotong yanjiu)
［Objective］ To further improve land use efficiency, reduce the fragmentation of urban space, enhance the regional urban image, and avoid the impact of regional transportation three-dimensional development and pedestrian system, it is necessary to conduct research on the key technologies for city railway underground depot structural design with reserved conditions for the overlying property development. ［Method］ In a case study of Shenkun Road Parking Lot Project of Shanghai City Railway Airport Link Line, based on the differences in structural design between the underground vehicle depot with reserved conditions for the overlying property development and the ground vehicle depot, the structural design challenges of the above-mentioned underground vehicle depot are studied, and the key technologies, such as the temperature cracks of super-long structures, structural waterproofing, and discontinuous construction structures in the construction process of the underground vehicle depot, are specifically analyzed. ［Result & Conclusion］ The anti-cracking reinforcing bars are configured according to the temperature stress results of the super-long cover plate without joints, theoretically restricting the concrete cracks and avoiding cracking and water leakage of the self-waterproof concrete. Alternative waterproofing solutions for the side walls and bottom plates from the structural aspect are proposed by the designer, against the possible water leakage caused by the construction quality, maintenance, closure conditions and the design differences. The optimal solution combining temporary anti-floating measures and the reservation of the construction load in the cover plate is proposed for the asynchronous construction of the underground vehicle depot structure and the overlying property development structure.